Parents and children in supermarkets: Incidence and influence. (January 2018) - Page, Bill; Sharp, Anne; Lockshin, Larry; Sorensen, Herb
Abstract: Children influence up to a fifth of all household purchase decisions, yet little is known about how this influence is brought to bear. This research looks at the primary householder purchase context of grocery shopping and establishes the incidence of children accompanying adult shoppers. It identifies the effect of their presence on the spend, time taken to complete the trip and the route taken in-store. More than 33, 000 observations are analysed, using exit interviews and structured observation of the in-store location of shoppers across two Australian states and four grocery retail outlets. Refuting the commonly held assertion that taking children shopping makes you spend more, accompanied shoppers do not spend more than unaccompanied shoppers, but rather shop 15% faster, tending to avoid busy areas in-store. We establish that, on average, 17% of grocery store shoppers are accompanied by children. Children are seen to accompany adults on both small and larger spend grocery shopping trips. Men, who are known to grocery shop less frequently than women, are found to have a lower incidence of being accompanied by a child when they do shop. This has implications for store layout and services offered. Products for children and parents need to be placed in areas where parents are more comfortable (that is, less busy areas), but also merchandised in ways that make it easy for parents to shop at their faster pace. The balance of these two needs is a direction for future research.